Development Of A Simulation Toolkit For Electrical Capacitance Tomography. - Hong, J H.; Saleh, J Mohamad (2004)
This paper describes a software tool that implements a two-dimensional finite element (FE) model for the simulation of capacitance readings from a specified electrical capacitance tomography (ECT) system.